Household Consumption, Inequality, and the Diffusion of E-Cigarettes in Indonesia - Maylaffayyaza Salmayusti Fajri; Estro Dariatno Sihaloho (Universitas Negeri Semarang, 2025)
Tobacco use remains one of Indonesia’s significant public health burdens, and the rapid growth of electronic cigarettes (e-cigarettes) introduces new regulatory challenges. Data from the 2018 Basic Health Research Survey (Riset Kesehatan Dasar; RISKESDAS) show that adolescent e-cigarette use increased sharply from 1.2% in 2016 to 10.9% in 2018. Drawing on consumer behaviour theory and the diffusion of innovations framework, this study examines how household consumption, income inequality, poverty, unemployment, and demographic factors influence e-cigarette uptake in Indonesia. Using nationally representative data from the 2023 National Socio-Economic Survey (Survei Sosial Ekonomi Nasional; SUSENAS), this study applies logistic regression and accounts for clustering at the provincial level. The results indicate that higher household consumption significantly increases the likelihood of e-cigarette use. Income inequality exhibits a strong positive association, suggesting diffusion driven by more affluent adopters, whereas unemployment and poverty show negative but statistically insignificant effects. E-cigarette adoption remains concentrated among men and urban residents. Overall, the findings indicate that the diffusion of e-cigarettes in Indonesia reflects underlying socioeconomic disparities. These results underscore the importance of policies addressing affordability and marketing practices—such as excise taxation, price floors, and integrated regulatory frameworks—to mitigate the expansion of nicotine-related inequalities and Indonesia’s existing tobacco burden.